PENGERINGAN PUFFING SAYURAN DENGAN GAS KARBON DIOKSIDA - Daniel Saputera (Jurnal Keteknikan Pertanian, 2006)
Abstract The objective of this research was to determine if CO2 puffing process could be applied to indonesian vegetables which resulted in the largest increase in bulk specific volume (BSV) and rehydration ratio (RR). This reseach also was intended to reduce the residence time and CO2 pressure needed to puff the product. Several vegetables wich were common in the indonesian’s instant food were puffed dried using CO2 gas at the pressure of 3.72, 5.10 and 6.48 Mpa and residence time of  4 and 8 minutes and were then dried using a fluidized bed drier.this technology had successfully dried the carrot, potato, andSiamese squash cube with the size of 6x6x6 mm3, and green bean chunk in the length of 6 mm. The bulk specific volume and rehydration ratio of the sample tried were significantly higher than the hot air dried one (1.3 to 5 times for BSV and 1.2 to 5 for RR) and were 0.6 to 0.95times the freeze dried product. The residence time, and pressure used for puffing with CO2 could be reduced by soaking the semple into 2% Na2HPO4, moisture content of  40 to 50%, residence time of 4 to 8 minutes, and CO2 pressure of 5.10 to 6.48 Mpa. Keyword: CO2, puffing, vegetable, rehydration ratio